2012
DOI: 10.1075/lab.2.2.01pat
|View full text |Cite
|
Sign up to set email alerts
|

Missing verbal inflections as a representational problem

Abstract: A continuing concern in second language acquisition (SLA) research is whether problems with inflectional morphology are representational or related somehow to performance. In this study, we examine 25 non-advanced learners of L2 Spanish and compare them with 18 native Spanish speakers on three grammatical structures: subject-verb inversion, adverb placement and person-number inflections on verbs. We use self-paced reading as a measure of underlying sensitivity to grammatical violations. Our results clearly sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 39 publications
(25 reference statements)
2
32
0
Order By: Relevance
“…Shibuya and Wakabayashi (2008) found longer RTs in position 0 (critical verb) in grammatical sentences than in ungrammatical sentences. Bannai (2011) andVanPatten et al (2012) found similar results in their research. The finding in both our Experiment 1 and Experiment 2 that RTs in position 1 were longer in grammatical sentences than in ungrammatical sentences is therefore not surprising.…”
Section: Discussionsupporting
confidence: 89%
“…Shibuya and Wakabayashi (2008) found longer RTs in position 0 (critical verb) in grammatical sentences than in ungrammatical sentences. Bannai (2011) andVanPatten et al (2012) found similar results in their research. The finding in both our Experiment 1 and Experiment 2 that RTs in position 1 were longer in grammatical sentences than in ungrammatical sentences is therefore not surprising.…”
Section: Discussionsupporting
confidence: 89%
“…The native speaker group exceeded 90% accuracy and were three times faster in responding to sentences than the learners, who performed at near chance, or even below, in detecting errors in the ungrammatical items. The large difference between the performance of native speakers and learners, including those who have had early immersive exposure, has been documented in previous work, as well (Bergström et al, 2016;Kersten, 2010), and poor sensitivity to nonnative morpho-syntactic errors in online sentence processing has also been reported (Chen et al, 2007;Jiang, 2004Jiang, , 2007Jiang et al, 2011;VanPatten et al, 2012). Considering the profiles of participants in the present study, the results illustrate how even for learners with very high global L2 proficiency and even for those who have had additional early immersive exposure, it is difficult to attain high sensitivity to L2 morpho-syntactic features in online processing.…”
Section: Sensitivity To L2 Morpho-syntactic Errors In Online Sentencesupporting
confidence: 57%
“…In VanPatten (1996), verb movement is discussed explicitly. The argument is that going from -VERB MOVEMENT to +VERB MOVEMENT does not require pedagogical intervention as the data in the input will cause the processing mechanisms to send the relevant data to the internal mechanisms (see VanPatten, Keating, & Leeser, 2012). The problem seems to be in going from + VERB MOVEMENT to -VERB MOVEMENT, as demonstrated by Trahey and White (1993).…”
Section: Discussionmentioning
confidence: 90%